Evaluasi Kualitas Software Modul Klaim Asuransi Group Life System dengan Model McCall - I Made Sugi Ardana; Yan Mitha Djaksana (CV. Multi Kreasi Media, 2022)
In today's digital era, insurance software is needed to help the operational process of insurance companies. Moreover, for life insurance companies that have a relatively large number of group customers, the claim module group life system software is a must. Insurance software can help support operational processes. Software quality is very important. Software quality is defined in two ways qualified requirements and user requirements. Many models can be used to evaluate software quality. One of them is to use the McCall model. Evaluation of software quality using the McCall model can be carried out in the product operation area, production revision area, and product transition area. Based on the evaluation results in this study, the quality of claim module group life system software in the product operation area is good with score 6,98 in the production revision area is good with score 7,47 in the product transition area is good with score 7,78.